Program Directors' Perceptions of Undergraduate Athletic Training Student Retention - Bowman, Thomas G. (J Athl Train, 2015)
CONTEXT: The average retention rate for students enrolled in undergraduate athletic training programs (ATPs) nationwide has been reported to be 81%, and slightly more than half of program directors (PDs) have indicated that retention of athletic training students (ATSs) is a problem. However, why PDs do or do not believe ATS retention is problematic is unknown. OBJECTIVE: To determine why PDs do or do not believe ATS retention is problematic. DESIGN: Qualitative study. SETTING: Undergraduate ATPs. PATIENTS OR OTHER PARTICIPANTS: We obtained responses from 177 of the 343 PDs (51.6%). Using data saturation as a guide, we randomly selected 16 PDs from the survey responses to participate in follow-up telephone interviews; 8 believed retention was a problem and 8 did not. DATA COLLECTION AND ANALYSIS: During audio-recorded telephone interviews, we asked PDs why they thought retention was or was not a problem for athletic training education. Following verbatim transcription, we used grounded theory to analyze the interview data and maintained trustworthiness by using intercoder agreement, member checks, and peer review. RESULTS: Program directors believed that retaining ATSs was a problem because students lack information regarding athletic training and the rigor of the ATP. Program directors were consistent in their perception that ATPs do not have a retention challenge because of the use of a secondary admissions process. This finding was likely based on personal use of a secondary admissions process in the ATPs these PDs lead. CONCLUSIONS: Program directors who lead ATPs that struggle to retain ATSs should consider using a secondary admissions process. During the preprofessional phase of the ATP, faculty and staff should work to socialize students to the demands of the ATP and the professional lives of athletic trainers.